2016
DOI: 10.1186/s12879-016-1550-y
|View full text |Cite
|
Sign up to set email alerts
|

Initiation and completion rates for latent tuberculosis infection treatment: a systematic review

Abstract: BackgroundControl of latent tuberculosis infection (LTBI) is an important step towards tuberculosis elimination. Preventive treatment will prevent the development of disease in most cases diagnosed with LTBI. However, low initiation and completion rates affect the effectiveness of preventive treatment. The objective was to systematically review data on initiation rates and completion rates for LTBI treatment regimens in the general population and specific populations with LTBI.MethodsA systematic review of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 102 publications
(90 reference statements)
2
52
0
Order By: Relevance
“…Outside of Japan, several systematic reviews on adherence for and outcomes of LTBI treatment have been conducted -for example, a review that was conducted for the WHO 2015 LTBI Guideline has concluded that treatment completion rates varied across different risk groups, ranging from 6-94%, with lower completion rates for prisoners and immigrant [12]. Another study which looked at studies from US and Canada has reported completion rates to be ranging between 22% and 90% [13], and a more recent review reported rates between 7-86%, both for foreign-born person [14]. A meta-analysis that was published in 2016 has estimated the pooled treatment completion rates for migrants to be 14.3% [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outside of Japan, several systematic reviews on adherence for and outcomes of LTBI treatment have been conducted -for example, a review that was conducted for the WHO 2015 LTBI Guideline has concluded that treatment completion rates varied across different risk groups, ranging from 6-94%, with lower completion rates for prisoners and immigrant [12]. Another study which looked at studies from US and Canada has reported completion rates to be ranging between 22% and 90% [13], and a more recent review reported rates between 7-86%, both for foreign-born person [14]. A meta-analysis that was published in 2016 has estimated the pooled treatment completion rates for migrants to be 14.3% [15].…”
Section: Discussionmentioning
confidence: 99%
“…As for the length of treatment regimen, while the WHO 2015 Guideline has concluded that longer treatment duration was detrimental to treatment completion, a systematic review that was published a year later has concluded that study results were inconclusive, with some showing better treatment outcomes for shorter regimens using rifampicin, pyrazinamide, rifabutin and/or INH, than the standard regimen (6 or 9 months of INH) while others showing similar completion rates, and also that the studies themselves were too heterogeneous to conduct pooled analysis [14]. In our study, the proportion of lost to follow-up was bigger among those who have started treatment with INH than those with RFP monotherapy (12.3% vs. 6.4%).…”
Section: Discussionmentioning
confidence: 99%
“…Age and gender did not impact rates of treatment completion in this study. Evidence for directly observed therapy (DOT) in LTBI treatment is inconsistent and not currently done at Calgary TB Services [19]. …”
Section: Discussionmentioning
confidence: 99%
“…Current WHO guidelines for low-burden countries recommend screening for LTBI for individuals who meet criteria for treatment if diagnosed with LTBI [3]. However, rates of treatment completion are often low, and vary widely between different settings, with heterogeneous factors observed to be associated with treatment noncompletion [4][5][6].…”
Section: Introductionmentioning
confidence: 99%